2016
DOI: 10.15740/has/ijas/12.1/15-21
|View full text |Cite
|
Sign up to set email alerts
|

Selection of superior genotypes in rice (Oryza sativa L.) through combining ability analysis

Abstract: : Combining ability analysis was studied in a line x tester analysis of rice (Oryza sativa L.). The analysis of variance for combining ability revealed that the variance due to GCA and SCA were highly significant for all the characters indicated that nonadditive gene actions were involved in the expression of the traits. Among the line AURC 14 and testers IR 64 and ADT 43 were considered as the best general combiners, while hybrids AURC 1 x ADT 36, AURC 8 x ADT 36, AURC 8 ADT 43, AURC 10 x ADT 43, AURC 14 x AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…RNR 28355 (3.26) was the best general combiner for characters such as days to 50% flowering, number of productive tillers per plant, number of grains per panicle, spikelet fertility and grain yield per plant, while RNR 26085 (3.09) was the best general combiner for plant height, number of productive tillers per plant, panicle length, kernel length and kernel breadth. These findings were supported bySatheeshkumar et al (2016) andAzad et al (2022).…”
supporting
confidence: 62%
“…RNR 28355 (3.26) was the best general combiner for characters such as days to 50% flowering, number of productive tillers per plant, number of grains per panicle, spikelet fertility and grain yield per plant, while RNR 26085 (3.09) was the best general combiner for plant height, number of productive tillers per plant, panicle length, kernel length and kernel breadth. These findings were supported bySatheeshkumar et al (2016) andAzad et al (2022).…”
supporting
confidence: 62%
“…The SCA variances recorded by Montazeri et al (2014) were higher than the GCA variances for panicle length and 1000-grain weight, suggesting that inheritance of these characters indicated predominance of non-additive gene action in the. Rahimi et al (2010), El-Refaee et al (2016, Rahaman (2016) and Satheeshkumar et al (2016) mentioned that, the analysis of variance for combining ability due to GCA and SCA were highly significant for days to heading, yield and its components characters indicated that both additive and non-additive gene effects contributed to the inheritance of the characters.…”
Section: Resultsmentioning
confidence: 99%